Interstitial Space and Trapped Sediment Drive Benthic Communities in Artificial Shell and Rock Reefs - Callaway, Ruth (Frontiers in Marine Science, 2018)
Enhancing habitat complexity and thereby biodiversity is a main motivation for the creation of artificial reefs in the marine and coastal environment. Uncertainty remains, however, regarding which types of reef best deliver this aim, and how material properties impact faunal communities. The objective of this study was to assess the macrobenthic infauna in standardised reef-units made from different types of shell and rock and to quantify factors explaining community properties. 70x75x25cm reef-units were made from cockle, mussel and oyster shells and rocks. Replicate units were placed on an intertidal sand flat of Swansea Bay (Wales, UK). After five months the benthic fauna was washed out of the reef-units and identified to species level. The volume of reef material, interstitial space and trapped sediment in each unit was quantified. A total of 45 invertebrate species were recorded in artificial reef-units compared with 12 species in the reef-free surrounding sands; 37 species were exclusively found in reefs. There was no significant difference between the infauna communities in different reef types in terms of univariate or multivariate diversity descriptors, but multivariate dispersion was lower among rock than shell-reef replicates. Distance-based linear models (DistLM) showed that the volume of interstitial space per reef-unit was the factor best explaining community structure, followed by properties of the trapped sediment. Species richness was significantly correlated with the volume of interstitial space and trapped sediment. Species seemed to use the reef-units fleetingly as shelter during low water, more permanently for protection, or as hunting ground for prey. The study demonstrated that artificial reef-units made of loose shell material and rocks can significantly enhance infauna diversity in sandy coastal environments. The identity of the material seems less relevant as long as it maximises interstitial space and allows trapping of sediment. This provides practitioners with a degree of creative freedom when designing artificial reefs with the aim to enhance infauna diversity.